336-341 Quaternary ammonium compound as bactericide in hide brine curing and presoaking processes - (:unkn) unknown (My University, 2012)
Inactivation of bacterial activity on hides is necessary during brine curing and presoaking processes. Therefore, bactericidal effect of 0.02% quaternary ammonium compound containing didecyl dimethyl ammonium chloride and benzyl dimethyl ammonium chloride on the mixed culture of Bacillus licheniformis, Bacillus pumilus, Enterococcus faecium, Staphylococcus intermedius, Pseudomonas luteola, Enterobacter cloacae and Vibrio fluvialis was examined in the test media containing 26% NaCl and organic substances by tube dilution method. In addition, the ability to grow of the mixed culture prepared from the test isolates was examined in the salt free Mueller Hinton Broth and in Mueller Hinton Broth containing 10%, 15% and 26% NaCl during 72 days. Bacterial count of the mixed culture in Mueller Hinton Broth containing 26% NaCl was found higher than those in the the salt free Mueller Hinton Broth media after 2,4 and 14 hours exposure times with the test agent. Our results showed that the test agent could be used in the brine solution where the salt slightly decreased effectiveness of the antibacterial agent. Additionally, it was observed that the isolates of the mixed culture were annihilated faster in the salt free Mueller Hinton Broth than the broth media containing different concentrations of NaCl. After the storage, bacterial counts in the Mueller Hinton Broth media containing different NaCl concentrations were not reduced to low levels. As a result, quaternary ammonium compound tested may be used in hide brine curing and presoaking processes to control Gram positive and Gram negative bacterial activities on hides. In addition, only NaCl application is not enough to control bacterial activity on hides.